Hubungan tingkat asupan sukrosa dalam sugar-sweetened beverage dengan overweight dan hyperglicemia pada mahasiswa Prodi Gizi UNESA - Suryanata, Selvia; Dini, Cleonara Yanuar (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: In the increasingly advanced era, advertisements for high-sugar foods and beverages are prevalent, which can negatively influence a person's behavior. It has been found that individuals may experience an increase in sugar-sweetened beverage consumption of up to 4,8 grams. The consumption of sugar-sweetened beverages has increased among undergraduate student, among nutrition students at UNESA, data show that approximately 48,46% frequently consume sugar-sweetened beverages more than five times per week. Excessive consumption of sugar-sweetened beverages significantly contributes to the incidence of overweight and hyperglycemia. This study is an extension that examines the sucrose content in sugar-sweetened beverages, building upon previous research that investigated the frequency of beverage consumption without considering their sucrose content.Objectives: To determine the relationship between sucrose intake from  sugar-sweetened beverages with overweight and hyperglycemia among Nutrition students at UNESA.Methods: A cross-sectional design was conducted on 95 students selected using stratified proportional purposive sampling. Data on sugar-sweetened beverage consumption were obtained through interviews using the SQ-FFQ. Fasting blood glucose (FBG) levels were measured using a glucometer. Nutritional status data were obtained from Body Mass Index (BMI) through measurements of height and weight. Bivariate data analysis was conducted using the Somers'd test.Results: 88,4% of respondents consumed a moderate amount sucrose intake from sugar-sweetened beverages (1–50 g/day), 76,8% had normal IMT  non-overweight (18,5-25 kg/m2), and 78,9% had normal fasting blood glucose  levels non-hypergycemia (< 90 mg/dL). There was a significant relationship between sucrose intake from sugar-sweetened beverage with overweight (P-value = 0,021; r = 0,407), but no significant relationship with hyperglycemia (P-value = 0,407) which is classified as a moderate correlation.Conclusion: There is a significant relationship between sucrose intake from sugar-sweetened beverage with overweight, but no significant relationship with hyperglycemia.